Prevalence of physical activity and dietary patterns as risk factors for cardiovascular diseases among semi-urban dwellers in Ibadan, Nigeria (2022)
Background: Physical inactivity and unhealthy diet are leading risk factors for cardiovascular diseases globally. Limited studies have assessed the prevalence of these risk factors in community-based settings in Nigeria. Objectives: This study assessed the prevalence of physical activity and the dietary pattern of residents in selected semi-urban communities in Ibadan, Nigeria. Methods: This was a cross-sectional study carried out among 500 randomly selected residents from two semi-urban communities. Multi-stage random sampling technique was used to select households and participants. Data were collected using a pretested modified version of the WHO STEPS instrument. Descriptive and inferential statistical analyses were determined at 5% level of significance. Results: The mean age was 35.36 ± 12.24 and a mean household size of 4.07 ± 1.85. Majority (87.2%) of the respondents engaged in low physical activity (< 150-300 min/wk). Consumption of fruits and vegetables was low among respondents at 33% and 36.4% respectively. The employment status of respondents was significantly related to expected workplace physical activity level (χ2=11.27; P=0.024). Conclusions: This study highlights the need for the development and implementation of community-driven, multi-layered public health promotion initiatives across different settings.